Optimization of genome editing through CRISPR-Cas9 engineering. Issue 3 (8th April 2016) - Zhang, Jian-Hua; Adikaram, Poorni; Pandey, Mritunjay; Genis, Allison; Simonds, William F.
ABSTRACT: CRISPR (Clustered Regularly-Interspaced Short Palindromic Repeats)-Cas9 (CRISPR associated protein 9) has rapidly become the most promising genome editing tool with great potential to revolutionize medicine. Through guidance of a 20 nucleotide RNA (gRNA), CRISPR-Cas9 finds and cuts target protospacer DNA precisely 3 base pairs upstream of a PAM (Protospacer Adjacent Motif). The broken DNA ends are repaired by either NHEJ (Non-Homologous End Joining) resulting in small indels, or by HDR (Homology Directed Repair) for precise gene or nucleotide replacement. Theoretically, CRISPR-Cas9 could be used to modify any genomic sequences, thereby providing a simple, easy, and cost effective means of genome wide gene editing. However, the off-target activity of CRISPR-Cas9 that cuts DNA sites with imperfect matches with gRNA have been of significant concern because clinical applications require 100% accuracy. Additionally, CRISPR-Cas9 has unpredictable efficiency among different DNA target sites and the PAM requirements greatly restrict its genome editing frequency. A large number of efforts have been made to address these impeding issues, but much more is needed to fully realize the medical potential of CRISPR-Cas9. In this article, we summarize the existing problems and current advances of the CRISPR-Cas9 technology and provide perspectives for the ultimate perfection of Cas9-mediated genome editing.